Relationship between insulin‐like growth factor‐1 receptor and human papillomavirus in patients with oropharyngeal cancer. Issue 7 (27th June 2014) - Matsumoto, Fumihiko; Fujimaki, Mitsuhisa; Ohba, Shinichi; Kojima, Masataka; Yokoyama, Junkichi; Ikeda, Katsuhisa
ABSTRACT Background Human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (SCC) is associated with better prognosis than HPV‐negative oropharyngeal SCC. The purpose of this study was to assess the expression of insulin‐like growth factor‐1 receptor (IGF‐1R) in patients with oropharyngeal SCC, its relationship to HPV status and various clinical parameters, and its relationship with clinical outcome. Methods The study subjects were 59 patients with oropharyngeal SCC. IGF‐1R expression was examined by immunohistochemistry in paraffin‐embedded tumor tissues. HPV status was evaluated by in situ hybridization (ISH) in the same tissues. Results IGF‐1R did not correlate with clinical parameters, but IGF‐1R expression was more common in HPV‐negative tumors than in HPV‐positive tumors. The prognosis was poorer in patients of the IGF‐1R‐positive group than in the IGF‐1R‐negative group. Conclusion The results suggested that IGF‐1R expression in oropharyngeal SCC correlated with poor prognosis in HPV‐negative patients. Treatment targeting IGF‐1R could potentially improve the survival of patients with HPV‐negative oropharyngeal SCC. © 2014 Wiley Periodicals, Inc. Head Neck 37: 977–981, 2015